IP-based real time video monitoring system with controllable platform - Zhuang, Hong; Wang, Zhaoqing (2006 2nd IEEE/ASME International Conference on Mechatronics and Embedded Systems and Applications, 2006)
The IP-based real time video surveillance system provides a way to monitor the scene on the spot at any time anywhere. An embedded system is as a sink of the system. The camera device is a front end. And the PC-based software is for the client. This weak coupling system is very flexible, efficient and low price. Using WAP technique, cell phone can be used as a client. This paper describes the system architecture, hardware and software structure